Food Production and Rural Development Division (FPRD) of the Commonwealth Secretariat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Food Production and Rural Development Division (FPRD) of the Commonwealth SecretariatBy 1992 50 countries had chosen to join the Commonwealth, an association of independent sovereign states, which have pledged to cooperate in the service of human...